Toxic or not toxic? The specifications of the standard ISO 10993-5 are not explicit enough to yield comparable results in the cytotoxicity assessment of an identical medical device - Gruber, Sarah; Nickel, Angela (Frontiers in Medical Technology, 2023)
Background Medical device manufacturers are obliged to prove the biocompatibility of their products when they come into contact with the human body. The requirements for the biological evaluation of medical devices are specified by the international standard series ISO 10993. Part five of this series describes the performance of in vitro cytotoxicity tests. This test evaluates the effects of medical device use on cell health. The existence of the specific standard suggests that the tests will produce reliable and comparable results. However, the ISO 10993-5 offers wide latitude in the test specifications. In the past, we noticed inconsistencies of the results from different laboratories. Objective To determine if the specifications of the standard ISO 10993-5 are explicit to ensure the comparability of test results and, if not, identify potential influencing factors. Methods An interlaboratory comparison was conducted for the in vitro cytotoxicity test according to ISO 10993-5. Fifty-two international laboratories evaluated the cytotoxicity for two unknown samples. One was polyethylene (PE) tubing, which is expected to be non-cytotoxic and the other was polyvinyl chloride (PVC) tubing, for which a cytotoxic potential was presumed. All laboratories were asked to perform an elution test with predefined extraction specifications. The other test parameters were freely chosen by the laboratories according to the guidelines set by the standard. Results To our surprise only 58 percent of the participating laboratories identified the cytotoxic potential of both materials as expected. Particularly for PVC a considerable variation of the results between the laboratories was observed [mean = 43 ± 30 (SD), min = 0, max = 100]. We showed that ten percent serum supplementation to the extraction medium, as well as longer incubation of the cells with the extract, greatly increased the test sensitivity for PVC. Conclusion The results clearly show that the specifications set by the ISO 10993-5 are not explicit enough to obtain comparable results for an identical medical device. To set requirements that ensure reliable cytotoxicity assessments, further research will be necessary to identify the best test conditions for specific materials and/or devices and the standard needs to be revised accordingly.